Photogrammetric techniques for characterisation of anisotropic mechanical properties of Ti-6Al-4V - Arthington, M (2010)
The principal aims of this research have been the development of photogrammetric techniques for the measurement of anisotropic deformation in uniaxially loaded cylindrical specimens. This has been achieved through the use of calibrated cameras and the application of edge detection and multiple view geometry. The techniques have been demonstrated at quasi-static strain rates, 10^-3 s^-1, using a screw-driven loading device and high strain rates, 10^3 s^-1, using Split Hopkinson Bars. The materials that have been measured using the technique are nearlyisotropic steel, anisotropic cross-rolled Ti-6Al-4V and anisotropic clock-rolled commercially pure Zr. These techniques allow the surface shapes of specimens that deform elliptically to be completely tracked and measured in situ during loading. This has allowed the measurement of properties that could not have been recorded before, including true direct stress and the ratio of transverse strains in principal material directions, at quasi-static and elevated strain rates, in tension and compression. The techniques have been validated by measuring elliptical prisms of various aspect ratios and independently measuring interrupted specimens using a coordinate measurement machine. A secondary aim of this research has been to improve the characterisation of the anisotropic mechanical properties of cross-rolled Ti-6Al-4V using the techniques developed. In particular, the uniaxial yield stresses, hardening properties and the associated anisotropic deformation behaviour along the principal material directions, have all been recorded in detail not seen before. Significant findings include: higher yield stresses in-plane than in the through-thickness direction in both tension and compression, and the near transverse-isotropy of the through-thickness direction for loading conditions other than quasi-static tension, where significant anisotropy was observed.